ANALISA KEKUATAN STRATEGI PEMASARAN MELALUI ONLINE MARKETING, OFFLINE MARKETING DAN SERVICE EXCELLENT TERHADAP LOYALITAS KONSUMEN PT. ADINATA GRAHA RAYA KALIWUNGU DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Basuk Cahyono; Andi Tri Haryono; Djamaludin Malik (Universitas Pandanaran, 2016)
The phenomenon of the higher land prices due to the increasing number of people to make the price ofthe property more expensive, but much needed. This research was conducted at PT. Adinata Graha Raya, aproperty development company in the region Kaliwungu, Kendal. Due to the economic growth has sloweddown, making capital-intensive sector sales slowed participate, the study tried to measure the effect of applyingpemsaran strategies through online, offline and culture of service excellence. Total population of 730 peoplewho are consumers who already buy and sell with PT. Adinata Graha Raya, with a sample of 100 people. Theresearch method is a method of quantitative analysis to measure the effect of variable Online Marketing, OfflineMarketing and Service Excellence to the Consumer Loyalty with Customer Satisfaction as an interveningvariable. Then processed using SPSS use test instruments, Classical Assumption Test, and Test RegressionCoefficients two stages. Research shows that a low Online has the most impact on consumer satisfaction thanvariables Offline and Service Excellence. Online Marketing strategies thus need for a strengtheningreinforcement without lowering Offline strategies and Service Excellence.Keywords: Online Marketing, Offline Marketing, Service excellent, customer satisfaction, customerloyalty